Animals : learn to draw with simple shapes and online tutorials - Kim, Heegyum (Drawing class (Quarry Books), 2023)
From Heegyum Kim, artist and author of Quarry's Draw 62...and Make Them Cute series, Drawing Class: Animals is a collection of 60 fun, beginner-level lessons for drawing animals in pencil, along with QR codes that link to video tutorials.